Pharmacological effect of Lidang Tang against adjuvant-induced rheumatoid arthritis in rats - Liu, Na; Lei, Tao; Liu, Xifang; Dong, Bo; Zeng, Xueqin; Sun, Yindi (Journal of the Hellenic Veterinary Medical Society, 2022)
Rheumatoid arthritis (RA) is a great concern across the globe. It is characterized as an autoimmune disease, where the body's immune system mistakenly attacks bone joints causing them to erode which leads to deformity in structure. Thus, the present study was conducted to elucidate the effect of Lidang Tang (LDT) decoction, a traditional Chinese medicine against rheumatoid arthritis. The rheumatoid arthritis was induced in Sprague-Dawley albino rats by intradermal injection of bovine collagen II type at the tail. Results suggested that LDT reduces paw swelling and arthritic scores in rats. The protective effect of LDT against RA was further substantiated by histopathological analysis of synovial tissue of rats, where LDT improves the architecture of the tissues as compared to CIA rats. It also reduces oxidative stress and inflammation in CIA rats as compared to the disease model group. The serum level of anti-collagen II-specific immunoglobulins (IgG1 and IgG2a) was reduced significantly in LDT treated group. In a western blot analysis, LDT treated group showed a significant reduction in the expression of NF-ĸB and COX-2 as compared to CIA rats. Collectively, our study for the first time demonstrated the protective effect of Lidang Tang decoction against rheumatoid arthritis.